2016
DOI: 10.5606/kbbihtisas.2016.34682
|View full text |Cite
|
Sign up to set email alerts
|

Validation and reliability of Turkish Singing Voice Handicap index

Abstract: The Turkish version of the Singing Voice Handicap Index is a valid and reliable scale which can be used in the evaluation of voice problems of Turkish-speaking singing voice users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…The mean score for healthy singers in the current study was 16.90 on the P-SVHI score, range 0 -100, which is similar to the results of healthy singers in Sobol et al, in which 729 healthy singers pooled from different languages had an average score of 14.10 on a 0 -100 scale (19). The mean P-SVHI score, range 0 -100, in healthy singers in the current study (16.9) also is similar to the results previously reported by (15), and Turkish (pathology group vs. healthy group: 53.6 ± 28.9 vs. 21.8 ± 18.5) (11). Also, the P-SVHI score (0 -100) for dysphonic subjects in our study was 40.9, which is more than the results for an Italian version in which dysphonic signers scored 31.68 (converted to 0-100), suggesting that voice disorder in our traditional singers is more than that in other style singers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The mean score for healthy singers in the current study was 16.90 on the P-SVHI score, range 0 -100, which is similar to the results of healthy singers in Sobol et al, in which 729 healthy singers pooled from different languages had an average score of 14.10 on a 0 -100 scale (19). The mean P-SVHI score, range 0 -100, in healthy singers in the current study (16.9) also is similar to the results previously reported by (15), and Turkish (pathology group vs. healthy group: 53.6 ± 28.9 vs. 21.8 ± 18.5) (11). Also, the P-SVHI score (0 -100) for dysphonic subjects in our study was 40.9, which is more than the results for an Italian version in which dysphonic signers scored 31.68 (converted to 0-100), suggesting that voice disorder in our traditional singers is more than that in other style singers.…”
Section: Discussionsupporting
confidence: 88%
“…The SVHI has been translated into various languages (3,(8)(9)(10)(11)(12)(13)(14)(15)(16). The validation of the P-SVHI was previously investigated by Ghaemi et al (15) in all singing styles.…”
Section: Introductionmentioning
confidence: 99%
“…Our search strategy identified 21 articles among the PubMed database. After screening using the phrases: singing voice handicap index (SVHI), adults and normal voices, and professional voice users, eight studies were identified 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 and therefore included. In Table 2 e characteristics of the studies are summarized.…”
Section: Resultsmentioning
confidence: 99%
“…Validation and adaptation of SVHI was done in many languages: English, 9 German, 12 Italian, 14 Turkish, 19 Spanish 13 and Polish. 18 Most of the studies considered small groups of healthy participants so it is very difficult to give a credible score of normative voices for singers.…”
Section: Discussionmentioning
confidence: 99%
“…Cronbach’s alpha was used to assess internal consistency with values above 0.7 indicating desirable levels. The Cronbach’s alpha cut-off were: 0.7 ≤ α < 0.8, Acceptable; 0.8 ≤ α < 0.9, Good; 0.9 ≤ α, Excellent 23 . Additionally, to investigate the psychometric properties of the items, inter-item association and Cronbach’s alpha with deleted items were also computed.…”
Section: Methodsmentioning
confidence: 99%